2016
DOI: 10.1042/bst20160069
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles of the bone morphogenetic protein pathway in cancer: potential therapeutic target for kinase inhibition

Abstract: Bone morphogenetic proteins (BMPs) belong to the transforming growth factor-β (TGF-β) family signalling pathway. Similar to TGF-β, the complex roles of BMPs in development and disease are demonstrated by their dichotomous roles in various cancers and cancer stages. Although early studies implicated BMP signalling in tumour suppressive phenotypes, the results of more recent experiments recognize BMPs as potent tumour promoters. Many of these complexities are becoming illuminated by understanding the role of BMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 154 publications
(199 reference statements)
0
56
0
1
Order By: Relevance
“…BMPs have divergent roles in cancer, acting as both suppressors and promoters of tumor progression under different circumstances. Based on the cell type and surrounding tumor microenvironment, BMPs take on differing actions in tumor biology (12). A positive correlation exists between BMP expression and clinical stages of cancer in human patients (13).…”
Section: Introductionmentioning
confidence: 99%
“…BMPs have divergent roles in cancer, acting as both suppressors and promoters of tumor progression under different circumstances. Based on the cell type and surrounding tumor microenvironment, BMPs take on differing actions in tumor biology (12). A positive correlation exists between BMP expression and clinical stages of cancer in human patients (13).…”
Section: Introductionmentioning
confidence: 99%
“…The complex functions of the BMP/FGF/TGF-β axis in development and disease have also been demonstrated by their dichotomous roles in various tumours and tumour stages [42] , suggesting that these molecules may be a valid target for cancer prevention and treatment.…”
Section: Othersmentioning
confidence: 99%
“…After the discovery that loss of BMPR1A leads to the development of Juvenile Polyposis [ 137 ], it was suggested that BMP signaling is tumor suppressive while classic TGF-β signaling is implicated in cancer pathogenesis. There is now increasing evidence that BMP signaling and BMPR2 play roles in tumor cell migration, metastasis, apoptosis, and local inflammation in a dynamic and complex manner, reviewed in [ 7 ]. For instance, breast cancer pathogenesis and BMP signaling appear to be related, with somewhat different results in human tissue versus mouse models.…”
Section: Bmpr2 Deficiency In Malignancymentioning
confidence: 99%
“…In the wake of the research that followed, the role of BMPR2 expanded beyond its origins in bone mineralization [ 3 ] to that of being a central key mediator of not only development but vascular homeostasis [ 4 , 5 ]. Beyond vascular biology, BMPR2 is necessary for development, organogenesis, and cancer pathogenesis [ 6 , 7 ]. Despite this, it remains strongly associated with its role in PAH pathogenesis, with an estimated 80% of familial and 20% of idiopathic PAH patients carrying a heterozygous BMPR2 mutation [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%